RuS2@CN-x with exposed (200) facet as a high-performance photocatalyst for selective C–C bond cleavage of biomass coupling with H–O bond cleavage of water to co-produce chemicals and H2. Issue 8 (4th April 2023) - Li, Xinze; Ma, Jiliang; Fu, Hongquan; Liu, Zhendong; Zhang, Junqiang; Cui, Rui; Guo, Yanzhu; Yao, Shuangquan; Sun, Runcang
Abstract : RuS2 @CN-x with exposed (200) facet as a high-performance photocatalyst for selective C–C bond cleavage of biomass coupling with H–O bond cleavage of water to co-produce chemicals and H2 . Abstract : The selective photocatalytic C–C bond cleavage of biomass coupling with H–O bond cleavage of water for co-producing chemicals and H2 is of great significance, but limited successes have been reported. In this study, a RuS2 @CN-x photocatalyst with only exposed crystal face (200) was prepared by anchoring RuS2 nanoparticles on carbon nitride (CN) nanosheets and successfully used in photocatalytic C–C bond cleavage of biomass-based sugars coupling with water splitting to co-generate lactic acid and hydrogen. Interestingly, the RuS2 (200) crystal face combined with the interfacial synergism between CN and RuS2 in RuS2 @CN-x effectively improved visible light absorption and enhanced the transfer/separation efficiency of photo-generated carriers. The RuS2 @CN-2 exhibited superior photocatalytic activity towards synchronous water splitting and biomass conversion to co-produce hydrogen (8698.3 μmol g −1 h −1 ) and lactic acid (91.5%). Furthermore, the experimental and DFT calculation results indicated that the exposed crystal face (200) of RuS2 significantly enhanced the photocatalytic activity of RuS2 @CN-2. Moreover, this reaction system not only has excellent recyclability but also displays excellent universality for small molecule biomass-derived monosaccharides and macromolecular xylan. This work provides a novel route to efficiently co-produce hydrogen and fine chemicals from photocatalytic C–C bond cleavage of biomass coupling with H–O bond cleavage of water.